EFFECTS INFLATION, HDI, CONSUMPTION, AND SOLAR SUBSIDIES ON POVERTY IN INDONESIA - Syarifah Syafira; Euridika Estefani Simalango (CV. Radja Publika, 2026)
This study carried out to view the effects of inflation and Human Development Index (HDI), diesel consumption, and diesel subsidies on poverty levels in Indonesia during 2006–2023. The data utilized in this study are secondary in nature. time-series data obtained from Central Statistics Agency and Ministry of Finance. The study applies multiple linear regression analysis was performed to test the classical assumptions and validate model. The results are inflation has a positive and significant effect on poverty, indicating that rising prices of goods and services reduce the purchasing power of low-income households and increase poverty levels. HDI have the positive not significant impact poverty, suggesting to signify on education, health, and living standards have not yet significantly reduced poverty during the study period. Diesel consumption stated a negative related in poverty, the impact not statistic significant, cause a change energy usage do not significantly influence poverty levels. Diesel subsidies also show have (-) but insignificant impact poverty, although they help maintain energy price stability and reduce the burden on low-income communities. Simultaneously, these four variables significantly affect Indonesia poverty, highlighting importance inflation control, Human Development Index improvement, effective diesel consumption and subsidy management as strategies for poverty reduction.